2006
DOI: 10.1007/s11064-006-9064-4
|View full text |Cite
|
Sign up to set email alerts
|

Long Lasting Effects of Electroconvulsive Seizures on Brain Oxidative Parameters

Abstract: This work was performed in order to determine the level of oxidative damage and antioxidant enzymes activities late after acute and chronic electroconvulsive shock (ECS) in rats. We measured oxidative parameters in hippocampus, cortex, and striatum, at 45, 60, 90 and 120 days after a single or multiple ECS. We demonstrated an increase in lipid peroxidation after multiple ECS in the hippocampus and striatum. This was also the case for protein carbonyls in the single or multiple protocols. In this way, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 20 publications
(36 reference statements)
1
20
1
Order By: Relevance
“…We have demonstrated that there is just a delayed increase in oxidative damage [13], but these findings require additional investigation in order to determine their clinical relevance.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…We have demonstrated that there is just a delayed increase in oxidative damage [13], but these findings require additional investigation in order to determine their clinical relevance.…”
Section: Introductionmentioning
confidence: 83%
“…In the first experimental step, animals received the traditional eight sessions ECS protocol [11][12][13]: an ECS session per day every other day. After the eighth ECS, the rats were exposed to weekly ECS on the first month, every 2 weeks on the second month and once a month on third month of maintenance.…”
Section: Animals and Study Designmentioning
confidence: 99%
“…Baricello et al (11) demonstrated an increase in catalase (CAT) and SOD activities, a decrease in lipid peroxidation, and protein damage in the hippocampus immediately after and up to 30 days after a single or multiple ECS. Feier et al (4) found a delayed increase in oxidative damage after ECS and a decrease in SOD and CAT activities in hippocampus and striatum in rats. Jornada et al [12] reported no alteration in the lipid peroxidation and no protein damage in the hippocampus, cortex, cerebellum, and striatum immediately after, 48 h and 7 days after the last maintenance ECS.…”
Section: Discussionmentioning
confidence: 97%
“…While some researchers found an increase (4) in oxidants, others measured a decrease (11); meanwhile, Jornada et al [12] reported no significant changes in oxidative metabolites after ECS. Regarding antioxidants, Erakovic et al (10) and Feier et al [4] measured a decrease, but Baricello et al (11) found an increase.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation